Systematic review and meta-analysis of interventions relevant for young offenders with mood disorders, anxiety disorders, or self-harm. - Townsend, E; Walker, D; Sargeant, S; Vostanis, P; Hawton, K; Stocker, O; Sithole, J (2010)
Background Mood and anxiety disorders, and problems with self-harm are significant and serious issues that are common in young people in the Criminal Justice System. Aims To examine whether interventions relevant to young offenders with mood or anxiety disorders, or problems with self-harm are effective. Method Systematic review and meta-analysis of data from randomised controlled trials relevant to young offenders experiencing these problems. Results An exhaustive search of the worldwide literature (published and unpublished) yielded 10 studies suitable for inclusion in this review. Meta-analysis of data from three studies (with a total population of 171 individuals) revealed that group-based Cognitive Behaviour Therapy (CBT) may help to reduce symptoms of depression in young offenders. Conclusions These preliminary findings suggest that group-based CBT may be useful for young offenders with such mental health problems, but larger high quality RCTs are now needed to bolster the evidence-base.